ANALISIS STRATEGI PENGEMBANGAN LEMBAGA KEUANGAN MIKRO SYARIAH (LKMS) PEDESAAN (STUDI KASUS BMT AL HASANAH SEKAMPUNG) - Irawan, Dedik; Affandi, Muhamad Irfan; Kalsum, Umi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research of analysis of the development strategy of Islamic microfinance institutions used SWOT analysis. This study aimed to analyze the internal and external environmental conditions and alternative strategies that can be applied in the development of Baitul Mal Wa TanWil (BMT) Al Hasanah Sekampung. The BMT internal environmental conditions showed that: 1) the level of education and skills of the management and employees were quite high and professionally, 2) the BMT has a strategic location, 3) the boards were very discipline, 4) the capital was used effectively, 5) product service very helpful members. Whereas, the five internal weaken factors were: 1) members who did not understand the concept of sharia, 2) the condition of the narrow building, 3) the administrative costs, 4) the capital owned cooperative was not great, 5), not all members could enjoy the service product. While the BMT external conditions were 1) the availability of capital from third parties, 2) the BMT adopt profit-sharing system, 3) the government regulations that support BMT, 4) the majority of local merchants, 5) the online transfer technology, 6) most of the capital third, 7) the increase of fuel prices, 8) the legislation government to the concept of sharia, 9) people did not understand the concept of Islamic and conventional, and 10) the cost of procurement. Based on the three obtained priority strategies, the highest priority strategic alternatives were a) improve the quality of care, b) officers and employees had a high level of education, and c) the cooperation with government and private agencies.